Hungarian Monitoring, 16 April 1989 . [Magyar rádiófigyelő], 1989. április 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Georgian domestic situation constantly improving Domestic Affairs: - Károly Grósz in Sofia - Hungarian Socialist Workers' Party (MSZMP) reform circles and Association of Young Intellectuals regard ministerial council as unsuitable for government - Participants at Kecskemét Reform Workshop urge extraordinary Party congress to be convened - Alliance of Free Democrats (SZDSZ) proposes creating government of experts - János Kádár's removal called for at Somogy County Party meeting - Mindszenty memoirs and recollections - Inconnu Artists' Group lay wooden headboard at plot 301 in Kerepesi Cemetery to turn it into a site of remembrance Külpolitika: - A grúz belpolitikai helyzet folyamatosan javul Belpolitika: - Grósz Károly Szófiában - Az MSZMP Reformkörök és a Fiatal Értelmiségiek Szövetsége alkalmatlannak tartja a Minisztertanácsot a kormányzásra - Rendkívüli pártkongresszus összehívását sürgették a résztvevők a kecskeméti Reformműhely-tanácskozáson - Az SZDSZ egy szakértői kormány létrehozására tett javaslatot - Kádár János leváltását követelik egy Somogy-megyei pártértekezleten - A kutatóé a szó: Mindszenty emlékiratok-visszaemlékezések - Az Inconnu Művészcsoport kopjafák elhelyezésével kívánják emléksírhellyé tenni a 301-es parcellát